Comparison of the Analytical and the Numerical Computations of the Slender Plates Subjected to the Interaction of In-plane and Out-of-plane Forces (Proceedings of Faculty of Civil Engineering, 2019)
In this work the numerical model for the out-of-plane geometrical nonlinearity of thin plane structures, subjected to the in-plane and the out-of-plane actions, is presented. First the large deformation theory was developed from the equilibrium, constitutive and kinematic problem conditions and then the numerical procedure for the general solution of the model was described. The procedure uses the finite element method implemented in the free software FEAP (Finite Element Analysis Program, University of California at Berkeley), in which our own code was incorporated using an iterative numerical procedure for solving problems of stability for generally-loaded flat thin plates. Some numerical examples are presented in this work.
Keywords: stability of flat plates; large deformation theory; finite element method; linked interpolation; FEAP program; numerical iteration